Аналіз нових ресурсозберігаючих технологічних процесів видавлювання тонкостінних деталей - Кротенко, Галина Анатоліївна (НТУ "ХПІ", 2013)
Стаття присвячена розробці методики розрахунку процесу видавлювання з квадратної заготованки деталі типу тонкостінних стаканів. Для цих процесів на базі варіаційного методу розроблені числові моделі, які необхідні для проектування технологічних процесів та штампів. На основі проведених досліджень розроблено технології, які дозволяють отримати тонкостінний стакан видавлюванням. Дані рекомендації щодо удосконалення конструкцій штампів.

The article is devoted to the manufacturing process of thin-walled extruded parts in a threedimensional metal flow. Based on the variational method was first developed a method of calculation of forming and power mode extrusion of the parts such as «thin-walled cans», a mathematical model of the process, the algorithms and computer programs we need for die design and manufacturing processes. Based on the developed techniques this model allows us to obtain thin-walled cans extrusion. Application of this technology instead of traditional allowed to raise quality of the parts. The results obtained in experimental studies have confirmed the adequacy of mathematical models of the extrusion of parts in a three-dimensional flow.
Keywords: тривимірна течія металу; варіаційний метод; штампове оснащення; розкочування; поле швидкості; формозмінення; tooling; forming; extrusion; variational method; velocity field; three-dimensional flow of metal